High-Brightness Double-Sided Transparent LED Display Based on MCPCB and Manufacturing Method Thereof
Patent Information
- Application Number
- KR1020250205749
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2045-12-22
Smart Images

Figure R1020250205749_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an LED display device, and more specifically, to a double-sided transparent LED display device and a method for manufacturing the same, wherein LEDs are patterned and arranged on both sides of a metal core printed circuit board (MCPCB), and a transparent area of at least 60% of the total area is secured so that images can be displayed independently on the front and back sides while maintaining transparency, and which has high brightness, low thermal deformation, and good heat dissipation. Background Technology
[0002] Recently, there has been an increasing demand for double-sided displays in fields such as advertising, exhibitions, and information display, which can show different images on the front and back of a single screen. In particular, transparent displays are attracting attention for their ability to display information while allowing the background to be visible, enabling them to be applied to shop windows, glass windows, and partitions to maximize space utilization.
[0003] Conventional transparent double-sided LED displays have primarily been implemented using transparent substrates. For example, International Patent Publication WO2016186468A1 discloses a transparent double-sided LED display in which electrode patterns are formed on both sides of a flexible transparent material (such as PET) and an LED chip is mounted using the COB (Chip On Board) method. While this transparent substrate method has the advantage of ensuring light transmittance, it had the following problems.
[0004] First, transparent substrates such as PET have low heat resistance (generally below 150°C), making it difficult to apply high-temperature Surface Mount Technology (SMT) processes. Conventional SMT processes require reflow temperatures of 185°C or higher, but transparent substrates undergo deformation at such high temperatures, making it difficult to implement fine pixel pitches.
[0005] Second, transparent substrates have very low thermal conductivity (approximately 0.2 W / mK in the case of PET), so they cannot effectively dissipate the heat generated during LED driving. In particular, heat accumulates during high-brightness driving, causing substrate deformation, which leads to pixel coordinate deviations, resulting in image quality degradation and display reliability issues.
[0006] Third, electromagnetic interference (EMI) and optical interference can occur between LEDs placed on both sides, and there was a lack of structural shielding means to block them.
[0007] Fourth, to ensure transparency, the area occupied by LEDs and circuit patterns must be minimized, but this presented a conflict with pixel density. In other words, there was a trade-off relationship where increasing transparency lowered pixel density and reduced resolution, while increasing pixel density reduced transparency.
[0008] Meanwhile, metal-core printed circuit boards (MCPCBs) are widely used in the LED lighting field to improve heat dissipation performance. MCPCBs use metals such as aluminum or copper as the substrate core to provide excellent thermal conductivity (generally 200 W / mK or higher) and have the advantage of enabling high-temperature SMT processes.
[0009] Although double-sided MCPCB technology has been developed, existing double-sided MCPCBs have primarily been used for lighting structures, where LEDs are placed on one side and driving or control circuits are placed on the opposite side. Furthermore, MCPCBs have been considered unsuitable for transparent displays because they are opaque due to their metal cores.
[0010] Therefore, there is a need to develop a double-sided transparent LED display technology that utilizes the excellent heat dissipation performance and high-temperature process suitability of MCPCB, while placing LEDs on both sides to display images independently on the front and back respectively, and simultaneously achieves transparency by securing a transparent area of more than 60%. The problem to be solved
[0011] The present invention was devised to solve the problems of the prior art as described above, and aims to realize a high-brightness double-sided transparent LED display by patterning an MCPCB (Metal Core Printed Circuit Board) to distinguish between an LED mounting area and a transparent area, and arranging LEDs in an alternating pattern on both sides.
[0012] Specifically, the present invention aims to achieve transparency and high brightness simultaneously by selectively forming a metal core substrate, an insulating layer, and a copper pattern layer only in the opaque area where an LED is mounted, and completely opening the remaining area to secure a transparent area of 60% or more of the total area.
[0013] In addition, the present invention aims to provide a double-sided transparent LED display and a method for manufacturing the same, wherein a metal core substrate provides electromagnetic shielding and optical blocking functions between LEDs on both sides while simultaneously performing excellent heat dissipation functions, thereby minimizing interference between the two sides and implementing a fine pixel pitch of 4 mm or less (preferably 3.91 mm or less) through a high-temperature SMT process, and suppressing substrate deformation and pixel coordinate changes caused by heat generated during LED driving, so as to stably achieve high brightness of 5000 nit or more while maintaining transparency.
[0014] In addition, the present invention aims to provide a high-brightness double-sided transparent LED display on an MCPCB substrate that satisfies both transparency and image quality by arranging LEDs on both sides in an alternating grid pattern and limiting the light emission angle to block optical interference between the light emission of one side LED and the LED on the other side, and optimizing the overlapping spacing between the upper LED and the lower LED to achieve a transparent area ratio of 60% or more.
[0015] Furthermore, the present invention aims to provide a transparent double-sided LED display that simultaneously secures mechanical strength and transparency by attaching an optical adhesive layer (OCA) maintaining a transmittance of 60% or more and a transparent glass on a transparent area, and has durability that allows for stable long-term use in indoor and outdoor environments. means of solving the problem
[0016] To achieve the above objectives, a high-brightness double-sided transparent LED display on an MCPCB substrate according to one embodiment of the present invention comprises: a metal core substrate made of aluminum material; an insulating layer formed on the upper surface and the lower surface of the metal core substrate, respectively; a copper pattern layer formed on the insulating layer, respectively; and a plurality of LEDs mounted on the copper pattern layer, respectively. The LEDs on the upper surface are arranged in a first grid pattern, and the LEDs on the lower surface are arranged in a second grid pattern positioned between the grid regions of the first grid pattern. The metal core substrate performs a heat dissipation function while providing electromagnetic shielding and optical blocking between the LEDs on the upper and lower surfaces. Additionally, a transparent area where the metal core substrate, insulating layer, and copper pattern layer are not formed is patterned and formed with an area ratio of 60% or more relative to the total area, thereby ensuring transparency while independently displaying images on the front and rear surfaces.
[0017] The transparent area can be configured such that it is regularly arranged between the opaque area on which the LED is mounted, so that the opaque area occupies 40% or less of the total area and the transparent area occupies 60% or more of the total area.
[0018] The metal core substrate has a thermal conductivity of 200 W / mK or higher, and it is possible to selectively form it only in the opaque area where the LED is mounted in order to secure the transparent area.
[0019] The insulating layer is formed from a composite material containing at least one of alumina, boron nitride, and aluminum nitride in an epoxy resin, and has an insulating breakdown voltage of 2 kV or more, and it is possible to ensure light transmittance by not forming an insulating layer in the transparent region.
[0020] It is possible to perform directional light emission control by limiting the light emission angle of the above LEDs to block optical interference between the light emission of one side LED and the LED on the other side, so that the front LED emits light only in the forward direction and the rear LED emits light only in the backward direction.
[0021] The pixel pitch between the LEDs is 4 mm or less, and due to the heat dissipation characteristics of the metal core substrate, substrate deformation and pixel coordinate changes caused by heat generated during LED driving are suppressed, making it possible to stably achieve high brightness of 5000 nit or more while maintaining transparency through the transparent area.
[0022] An optical adhesive layer maintaining a transmittance of 60% or more is formed on the above transparent area, and a transparent glass is attached to the above optical adhesive layer, making it possible to simultaneously secure mechanical strength and transparency.
[0023] Meanwhile, a method for manufacturing a high-brightness double-sided transparent LED display on an MCPCB substrate according to one embodiment of the present invention comprises: a step of preparing a metal core substrate made of aluminum material, and designing an LED mounting area by patterning it so that a transparent area occupies 60% or more of the total area; a step of forming an insulating layer on an upper surface and a lower surface corresponding to the LED mounting area of the metal core substrate; a step of forming a copper pattern layer on the insulating layer; a step of mounting a plurality of LEDs in a first grid pattern on the copper pattern layer on the upper surface using an SMT process; and a step of mounting a plurality of LEDs in a second grid pattern on the copper pattern layer on the lower surface using an SMT process so as to be positioned between the grid areas of the first grid pattern; wherein the SMT process is performed at a temperature of 185 degrees or higher, and the metal core substrate dissipates heat generated during the SMT process and when driving the LED to prevent thermal deformation of the substrate, while securing a light transmittance of 60% or more through the transparent area.
[0024] The step of mounting LEDs in the second grid pattern is to mount them by precisely aligning them so that the LED on the upper surface and the LED on the lower surface do not overlap when projected vertically, and the overlap spacing between the upper surface LED and the lower surface LED is set so that the area ratio of the transparent area achieves 60% or more of the total area, thereby making it possible to maximize the transparent area while preventing mutual optical interference.
[0025] It is possible to further include the step of applying an optical adhesive layer with a transmittance of 60% or more on a transparent area after mounting LEDs on the upper and lower surfaces; and the step of attaching a transparent glass on the optical adhesive layer. Effects of the invention
[0026] The MCPCB substrate high-brightness double-sided transparent LED display and the method for manufacturing the same according to the present invention have the following effects.
[0027] First, by patterning the MCPCB to form a metal core substrate, an insulating layer, and a copper pattern layer only in the LED mounting area and completely leaving the remaining area open, a transparent area of more than 60% of the total area can be secured, thereby providing excellent transparency while enabling double-sided display functionality.
[0028] Second, the metal core substrate of the MCPCB provides electromagnetic shielding and optical blocking functions between the LEDs on both sides, effectively minimizing interference between the two sides and enabling the display of high-quality images independently on the front and back sides.
[0029] Third, by utilizing the excellent heat resistance of the MCPCB, a high-temperature SMT process of 185 degrees or higher can be applied, so a fine pixel pitch of 4 mm or less (preferably 3.91 mm or less) can be precisely realized, which corresponds to a very high resolution for a transparent display.
[0030] Fourth, due to the high thermal conductivity (over 200 W / mK) of the MCPCB, heat generated during LED driving can be effectively dissipated. Consequently, substrate deformation and pixel coordinate changes are suppressed even during high-brightness driving (over 5,000 nits), allowing for the maintenance of stable image quality over a long period. This is in contrast to existing PET-based transparent displays, which suffer from thermal deformation issues during high-brightness driving.
[0031] Fifth, by arranging the LEDs on both sides in an alternating grid pattern and limiting the light emission angle, the light emission from one side of the LED is effectively blocked from optically interfering with the LED on the other side, and by optimizing the overlapping spacing between the top LED and the bottom LED to secure a transparent area of 60% or more, transparency and image quality can be satisfied simultaneously.
[0032] Sixth, by attaching an optical adhesive layer (OCA) with a transmittance of 60% or more and transparent glass to the transparent area, mechanical strength can be secured and durability against external impacts or environmental changes can be improved, and integrated installation is possible in various architectural spaces such as show windows, glass partitions, and exhibition halls.
[0033] Seventh, compared to the existing fully transparent substrate method, it offers superior heat dissipation performance and facilitates the implementation of fine pitch, making it effectively applicable to outdoor transparent advertising displays, building exterior glass window displays, and shopping mall glass partition displays that require high brightness.
[0034] Eighth, by implementing a double-sided transparent display using a patterned MCPCB structure, the manufacturing process is simplified and more economical compared to the method of back-combining two separate transparent displays, and the display thickness can be made thinner, resulting in high installation space efficiency.
[0035] Ninth, by securing a transparent area of more than 60%, the background or product behind the display can be naturally seen while video information can be displayed, thus opening up new application fields such as shop window displays, transparent screens for exhibitions, and architectural media facades.
[0036] Tenth, with a single MCPCB patterned structure, different content can be displayed on the front and back, which offers high space utilization, excellent information delivery efficiency relative to the installation area, and can double advertising profitability. Brief explanation of the drawing
[0037] FIG. 1 is a cross-sectional structure of an MCPCB substrate high-brightness double-sided transparent LED display according to the present invention. FIG. 2 is a plan view showing a grid arrangement structure and a transparent area of a double-sided LED according to the present invention, showing that a first grid pattern on the upper surface and a second grid pattern on the lower surface are arranged in an alternating manner and a transparent area is formed between them. FIG. 3 is a front view showing a grid arrangement structure of a double-sided LED according to the present invention, illustrating a relationship in which the LED on the upper surface and the LED on the lower surface do not overlap when projected vertically. FIG. 4 is a detailed diagram showing a structure for limiting the light emission angle of an LED according to the present invention, illustrating the principle of blocking optical interference between the light emission of an LED on one side and an LED on the other side. FIG. 5 is a cross-sectional view showing the detailed stacked structure of an MCPCB substrate according to the present invention and a structure in which an optical adhesive layer and transparent glass are attached to a transparent region. FIG. 6 is a process flowchart illustrating a method for manufacturing a high-brightness double-sided transparent LED display on an MCPCB substrate according to the present invention. Specific details for implementing the invention
[0038] Hereinafter, various embodiments and / or aspects are disclosed with reference to the drawings. For illustrative purposes, numerous specific details are disclosed in the following description to aid in a general understanding of one or more aspects. However, it will also be recognized by those skilled in the art that these aspects may be practiced without such specific details. The following description and the accompanying drawings describe specific exemplary aspects of one or more aspects in detail. However, these aspects are exemplary, and some of the various methods in the principles of the various aspects may be used, and the description is intended to include all such aspects and their equivalents.
[0039] As used herein, terms such as "examples," "examples," "aspects," "examples," etc., may not be interpreted as implying that any aspect or design described is better or more advantageous than other aspects or designs.
[0040] Additionally, the terms “comprising” and / or “comprising” should be understood to mean that the relevant feature and / or component is present, but not to exclude the presence or addition of one or more other features, components and / or groups thereof.
[0041] Additionally, terms including ordinal numbers, such as first, second, etc., may be used to describe various components, but said components are not limited by said terms. Such terms are used solely for the purpose of distinguishing one component from another. For example, without departing from the scope of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component. The term "and / or" includes a combination of a plurality of related described items or any of a plurality of related described items.
[0042] Furthermore, in the embodiments of the present invention, all terms used herein, including technical or scientific terms, unless otherwise defined, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in the embodiments of the present invention.
[0043] FIG. 1 is a cross-sectional view showing the structure of a high-brightness double-sided transparent LED display on an MCPCB substrate according to the present invention; FIG. 2 is a plan view showing the grid arrangement structure and transparent area of a double-sided LED according to the present invention, showing that a first grid pattern on the upper surface and a second grid pattern on the lower surface are arranged in an alternating manner and a transparent area is formed between them; FIG. 3 is a front view showing the grid arrangement structure of a double-sided LED according to the present invention, showing the relationship in which the LED on the upper surface and the LED on the lower surface do not overlap when projected vertically; FIG. 4 is a detailed view showing the structure of limiting the light emission angle of an LED according to the present invention, showing the principle of blocking optical interference between the light emission of an LED on one surface and an LED on the other surface; FIG. 5 is a cross-sectional view showing the detailed stacking structure of an MCPCB substrate according to the present invention and a structure in which an optical adhesive layer and a transparent glass are attached to a transparent area; FIG. 6 is a process flowchart showing a method for manufacturing a high-brightness double-sided transparent LED display on an MCPCB substrate according to the present invention.
[0044] Meanwhile, in the following description, some components described in the drawings may be omitted or excessively enlarged or reduced in order to explain the function of each component of the present invention, but it will be understood that such illustrated components do not limit the technical features and scope of rights of the present invention.
[0045] In addition, in the following description, multiple drawings will be referred to simultaneously to explain a single technical feature or a component constituting the invention.
[0046] Referring to FIGS. 1 to 6, the MCPCB substrate high-brightness double-sided transparent LED display according to the present invention comprises a metal core substrate (100) made of aluminum material, insulating layers (110, 120) respectively formed on the upper and lower surfaces of the metal core substrate (100), copper pattern layers (130, 140) respectively formed on the insulating layers (110, 120), and a plurality of LEDs (150, 160) respectively mounted on the copper pattern layers (130, 140). The LEDs (150) on the upper surface are arranged in a first grid pattern, and the LEDs (160) on the lower surface are arranged in a second grid pattern positioned between the grid regions of the first grid pattern. The metal core substrate (100) performs a heat dissipation function while providing electromagnetic shielding and optical blocking between the LEDs (150, 160) on the upper and lower surfaces. The metal core substrate (100) and the insulating layers (110, 120) A transparent area (170) in which the copper pattern layer (130, 140) is not formed is patterned and formed with an area ratio of 60% or more of the total area, thereby having a structure that ensures transparency while independently displaying images on the front and back sides.
[0047] This structure is a fundamentally different approach from the conventional transparent substrate method and the completely opaque MCPCB method, and has technical significance in that it simultaneously achieves transparency and high-brightness double-sided display functions by securing a transparent area (170) through patterning while utilizing the excellent heat dissipation performance and electromagnetic shielding characteristics of the MCPCB.
[0048] First, the metal core substrate (100) will be described in detail. In the present invention, the metal core substrate (100) is selectively formed only in the opaque area where the LED (150, 160) is mounted, and the area where the LED is not mounted is completely open to form a transparent area (170). Unlike conventional continuous metal substrates, this has a patterned structure and corresponds to the core structural feature of the present invention. The metal core substrate (100) is formed from aluminum material because it can simultaneously secure excellent thermal conductivity and cost-effectiveness. Aluminum is a representative lightweight metal with a density of only about 2.7 g / cm³, which is advantageous for lightweighting displays, and its thermal conductivity is about 237 W / mK for pure aluminum and a high value of 200 W / mK or more for alloys.
[0049] In the present invention, the metal core substrate (100) has a thermal conductivity of 200 W / mK or higher and is selectively formed only in the opaque area where the LED (150, 160) is mounted in order to secure the transparent area (170). This is to rapidly dissipate heat generated when driving the LED (150, 160) to suppress substrate deformation and pixel coordinate changes. Thermal conductivity is a physical property that indicates the ability of a material to transfer heat, and its unit is W / (m·K). The higher the thermal conductivity, the faster heat is transferred, which can prevent localized overheating. The thermal conductivity of aluminum, 200 W / mK, is more than 1,000 times higher than the thermal conductivity of PET, which is about 0.2 W / mK, and this large difference enables the excellent heat dissipation performance of the present invention.
[0050] Types of aluminum alloys that can be used as metal core substrates (100) include 3003 alloy, 5052 alloy, and 6061 alloy, and their respective characteristics are as follows. 3003 alloy has excellent formability and corrosion resistance with manganese as the main alloying element, and although its thermal conductivity is about 162 W / mK, which is lower than that of pure aluminum, it provides sufficient heat dissipation performance. 5052 alloy has high strength and excellent corrosion resistance with magnesium as the main alloying element, and is particularly suitable for outdoor display applications due to its excellent durability in coastal areas or salty environments. 6061 alloy has magnesium and silicon as the main alloying elements, and its strength can be increased through heat treatment, making it suitable for large displays requiring structural stability. Depending on the embodiment, copper may also be used as the metal core substrate (100). Although copper has a higher thermal conductivity (about 398 W / mK) than aluminum, it has the disadvantage of increasing weight and cost, so it can be selectively applied for ultra-high brightness displays requiring extreme heat dissipation performance.
[0051] The thickness of the metal core substrate (100) is generally selected in the range of 0.8 mm to 3.0 mm, and preferably has a thickness of 1.0 mm to 1.5 mm. If the thickness is too thin, mechanical strength is insufficient, which may cause sagging when manufacturing a large-area display, and if the thickness is too thick, the overall thickness of the display increases and the weight increases excessively, making it disadvantageous for installation and transportation. In an embodiment of the present invention, a 1.0 mm thick aluminum substrate is used to ensure a balance between heat dissipation performance and mechanical strength.
[0052] One of the important functions of the metal core substrate (100) is that it provides electromagnetic shielding and optical blocking between the LEDs (150, 160) on the upper and lower surfaces. Electromagnetic shielding is naturally achieved because the metal core substrate (100) is conductive, and metals such as aluminum or copper have excellent shielding effects against electromagnetic waves, preventing electromagnetic signals generated from the LEDs (150) on the upper surface from interfering with the LEDs (160) on the lower surface. This is particularly important in fine pixel pitch displays where LEDs are arranged at high density, because the closer the distance between LEDs, the higher the likelihood of electromagnetic interference (EMI). Since electromagnetic interference can cause the driving circuit of the LEDs to malfunction or noise to appear on the screen, shielding by the metal core substrate (100) is essential for ensuring signal integrity.
[0053] The optical blocking function is derived from the characteristic that the metal core substrate (100) is an opaque metal material. By completely blocking light, the metal core substrate (100) fundamentally prevents light generated from the LED (150) on the upper surface from penetrating the metal core substrate (100) and reaching the LED (160) area on the lower surface. This is highly effective in eliminating optical crosstalk between the two sides and contributes to increasing the independence and contrast ratio of the image displayed on each side. In the present invention, since the metal core substrate (100) is selectively formed only in the LED mounting area, it is possible to implement a transparent display by providing a complete shielding function in that area while allowing light to pass through the transparent area (170).
[0054] The transparent area (170) is a core component of the present invention and refers to a completely open space where the metal core substrate (100), insulating layer (110, 120), and copper pattern layer (130, 140) are not formed. As can be seen in FIGS. 1, 2 and 5, the transparent area (170) is regularly arranged between opaque areas where LEDs (150, 160) are mounted. The transparent area (170) is regularly arranged between opaque areas where LEDs (150, 160) are mounted, so that the opaque area occupies 40% or less of the total area and the transparent area (170) occupies 60% or more of the total area. This area ratio is a threshold value for ensuring practicality as a transparent display; if the transparent area (170) is less than 60%, the visibility of the background is reduced, and the effect as a transparent display is reduced, and if the transparent area (170) is excessively increased, the pixel density is lowered, and there is a problem of degraded image quality. Therefore, the figure of 60% or more of the transparent area (170) corresponds to an optimized design standard that considers the balance between transparency and image quality.
[0055] The formation of the transparent region (170) is achieved through the patterning of the metal core substrate (100). Patterning refers to a process of creating a specific pattern by partially removing or selectively forming a continuous substrate. In the present invention, this is achieved by forming the metal core substrate (100) only at the location where the LED (150, 160) is to be mounted, while the remaining area is completely removed or not formed from the beginning. Specific methods for the patterning process may include laser cutting, CNC milling, chemical etching, waterjet cutting, and punching. Laser cutting is a method of precisely cutting metal using a high-power laser beam; it is suitable for forming fine patterns because it has a small heat-affected zone (HAZ) and high cutting precision. Types of lasers include CO2 lasers, fiber lasers, and Nd:YAG lasers, and fiber lasers are effective for metals with high reflectivity, such as aluminum. CNC milling is a machining method that removes metal using a rotating cutting tool; it enables large-area processing and offers high productivity. Desired shapes can be machined using end mills or drill bits, and precise patterns can be implemented through Computer Numerical Control (CNC). Chemical etching is a method that forms a protective film on the metal surface and then selectively removes exposed areas using an etching solution; it enables the formation of complex patterns and offers good compatibility with PCB manufacturing processes. Sodium hydroxide (NaOH) or hydrochloric acid (HCl) aqueous solutions are generally used for aluminum etching. Waterjet cutting is a method that cuts metal using a high-pressure stream of water; it has the advantage of not generating heat, thus preventing changes in material properties. Cutting performance is enhanced by using an abrasive waterjet, which mixes abrasives with water. Punching is a method of punching out metal sheets using a press die, offering high cost-effectiveness for mass production.However, since punching requires initial mold manufacturing costs, it is suitable for mass production, but there may be limitations in implementing fine patterns.
[0056] The size and arrangement of the transparent area (170) are closely related to the pixel pitch of the LEDs (150, 160). In the present invention, the pixel pitch between LEDs is 4 mm or less, preferably 3.91 mm or less. Pixel pitch refers to the distance between the centers of two adjacent LEDs, and the smaller this value, the higher the resolution can be achieved. When the pixel pitch is 4 mm, the area occupied by each pixel is 4 mm × 4 mm = 16 mm², and since the opaque area occupies 40% or less of this, approximately 6.4 mm² or less corresponds to the LED mounting area, and the remaining 9.6 mm² or more corresponds to the transparent area (170). As a more preferred embodiment, when the pixel pitch is 3.91 mm, each pixel area is approximately 15.29 mm², the opaque area is approximately 6.12 mm² or less, and the transparent area (170) is approximately 9.17 mm² or more. Through this design, high resolution and transparency can be achieved simultaneously. The finer the pixel pitch, the higher the resolution can be provided. For example, based on a pixel pitch of 3.91 mm, about 256 pixels can be arranged at a distance of 1 meter, which is a resolution sufficient to provide a clear image at a medium viewing distance (about 4-8 m).
[0057] Insulating layers (110, 120) are formed on the upper and lower surfaces of the metal core substrate (100), respectively. The insulating layers (110, 120) provide electrical insulation between the metal core substrate (100) and the copper pattern layer (130, 140) formed thereon, while simultaneously serving to effectively transfer heat from the LED (150, 160) to the metal core substrate (100). In the present invention, the insulating layers (110, 120) are selectively formed only in the LED mounting area where the metal core substrate (100) is formed, and no insulating layer is formed in the transparent area (170) to ensure light transmittance. The insulating layers (110, 120) are formed from a composite material containing at least one of alumina, boron nitride, and aluminum nitride in an epoxy resin, have an insulating breakdown voltage of 2 kV or more, and no insulating layer is formed in the transparent area (170) to ensure light transmittance.
[0058] The composite material composition of the insulating layer (110, 120) is described in detail. The epoxy resin serves as the basic matrix and provides excellent insulation properties and adhesion. The epoxy resin is a thermosetting resin having epoxy groups, and by reacting with a curing agent to form a three-dimensional network structure, it possesses excellent mechanical strength and chemical stability. Although the thermal conductivity of the epoxy resin itself is low at approximately 0.2 W / mK, the thermal conductivity can be improved by adding ceramic fillers. Alumina (Al O₃ is the most commonly used ceramic filler, possessing a thermal conductivity of approximately 25-30 W / mK and excellent insulation and heat resistance. Alumina is suitable for mass production due to its low cost and ease of processing, and it also exhibits excellent wear resistance due to its high hardness. Alumina fillers come in various shapes, such as spherical, platelet, and needle forms; spherical fillers can increase the packing density, while platelet fillers can provide directional heat conduction. Boron nitride (BN) has a thermal conductivity of approximately 60-250 W / mK, which is higher than that of alumina; in particular, hexagonal boron nitride (h-BN) exhibits excellent thermal conductivity due to its layered structure. Boron nitride possesses unique characteristics, simultaneously possessing high thermal conductivity and excellent electrical insulation, and exhibits excellent thermal cycle stability due to its low coefficient of thermal expansion. Aluminum nitride (AlN) has a very high thermal conductivity of approximately 170–230 W / mK and is a preferred material for high-brightness LED applications. Since aluminum nitride maintains insulation while having a thermal conductivity about 6–8 times higher than alumina, it is ideal for high-power LED displays. However, because aluminum nitride can hydrolyze and degrade in performance when exposed to moisture, surface treatment or encapsulation processes are important.
[0059] These ceramic fillers are added to the epoxy resin in a range of 30–70 wt%; while a higher filler content increases thermal conductivity, it can also reduce mechanical strength, so a proper balance is required. Generally, a filler content of 40–60 wt% is selected for optimal thermal conductivity and mechanical properties. The particle size distribution of the filler is also important; mixing particles of various sizes allows smaller particles to fill the voids between larger particles, thereby increasing packing density. Thermal conductivity can be further improved through this optimization of particle packing.
[0060] Dielectric strength of the insulating layer (110, 120) must be at least 2 kV to protect the circuit from transient voltages or surge voltages that may occur during LED driving. Dielectric strength refers to the maximum electric field strength that an insulator can withstand without being destroyed, and the unit is expressed as kV / mm. Dielectric strength is determined by the thickness of the insulating layer (110, 120) and the dielectric strength of the material, and generally, the thickness of the insulating layer (110, 120) is selected in the range of 50 μm to 200 μm. In an embodiment of the present invention, an insulating layer (110, 120) with a thickness of 100 μm is used, which simultaneously satisfies a thermal conductivity of 2.0 W / mK and a dielectric strength of 2-4 kV. If the insulating layer (110, 120) is too thin, the dielectric strength may be insufficient, and if it is too thick, the thermal resistance may increase, which may degrade heat dissipation performance. Thermal resistance is an indicator of the degree to which heat flow is hindered, and its unit is K / W. The thermal resistance of an insulating layer is proportional to its thickness and inversely proportional to its thermal conductivity. Therefore, the thickness of the insulating layer (110, 120) must be optimized by considering the trade-off between electrical insulation and thermal conduction.
[0061] The manufacturing process of the insulating layer (110, 120) generally uses the prepreg method. Prepreg is an abbreviation for pre-impregnated, meaning a semi-cured composite material in which resin is pre-impregnated into a fiber or substrate. A slurry of mixed epoxy resin and ceramic filler is impregnated into a glass fiber or film substrate and then made semi-cured to provide a sheet form. This is then laminated onto both sides of a metal core substrate (100) and finally cured by applying heat and pressure. The lamination process is generally performed at a temperature of 150-180 degrees Celsius, and a pressure in the range of 10-50 bar is applied. Using a vacuum environment during lamination can prevent bubble formation and improve adhesion quality. After curing, a strong adhesive force is formed between the insulating layer (110, 120) and the metal core substrate (100), forming a stable laminated structure without peeling. The adhesive force is generally evaluated by a tensile peel test, and a peel strength of 1.0 N / mm or more is required.
[0062] Copper pattern layers (130, 140) are formed on the insulating layers (110, 120), respectively. The copper pattern layers (130, 140) form an electrical circuit that supplies power and signals to the LED (150, 160), and a copper foil (1 oz) with a thickness of 35 μm is generally used. Copper has a very high electrical conductivity of about 5.96 x 10⁷ S / m and excellent thermal conductivity of about 398 W / mK, making it ideal as a material for forming electrical circuits. Copper has the second highest electrical conductivity after silver (6.30 x 10⁷ S / m), and is widely used industrially because it is cheaper and easier to process than silver. For high-brightness LED applications requiring high current, a thick copper foil of 70 μm (2 oz) or 105 μm (3 oz) may be used, which has the effect of increasing current capacity and reducing heat generation. As the thickness of the copper foil increases, the electrical resistance decreases, reducing I²R loss (Joule heat) and allowing more current to flow safely.
[0063] The process of forming the copper pattern layer (130, 140) proceeds similarly to a general PCB manufacturing process. First, a copper foil is laminated onto an insulating layer (110, 120), a photoresist is applied, and then exposed using a mask with a desired circuit pattern drawn on it. Photoresist is a photosensitive resin whose chemical properties change when exposed to light, and there are negative and positive types. With negative photoresist, the exposed area hardens and remains while the unexposed area is removed, whereas with positive photoresist, the opposite is true. After exposure, when developed using a developer, only the circuit pattern area is protected and the remaining area is removed. Generally, an alkaline aqueous solution (sodium carbonate or sodium hydroxide solution) is used as the developer. Subsequently, unnecessary copper is removed through an etching process to form the final circuit pattern. Chemical etching using ferric chloride (FeCl3) or ammonium persulfate ((NH4)2S2O8) is generally used as the etching method. Ferric chloride etching can be performed at room temperature and has a fast etching rate, but it has the disadvantage that the etching solution is difficult to regenerate. Ammonium persulfate etching allows for easy management of the etching solution and enables uniform etching, but temperature control is important. When a fine pattern is required, alkaline etching (ammonia-based) may be used, which has excellent pattern verticality due to minimal side etching. After etching, the residual photoresist is stripped and cleaned to obtain the final copper pattern layer (130, 140). Organic solvents or alkaline strippers are generally used for stripping.
[0064] The circuit design of the copper pattern layer (130, 140) is closely related to the arrangement pattern of the LEDs (150, 160). Each LED (150, 160) requires an anode and a cathode connection so that it can be controlled individually, and for this purpose, a complex wiring pattern is required. In particular, at fine pixel pitches, the spacing between wires becomes very narrow, so precise control of the minimum line width and minimum space is required. In the embodiment of the present invention, a minimum line width of 0.1 mm and a minimum space of 0.1 mm are implemented, which is a level that is sufficiently achievable with a standard MCPCB manufacturing process. If a finer pattern is required, a semi-additive process (SAP) or a modified semi-additive process (mSAP) can be used, through which ultra-fine patterns with a line width / space of 50 μm or less can be implemented.
[0065] Surface treatment is performed on the surface of the copper pattern layer (130, 140) to prevent oxidation and improve solderability. Surface treatment methods include HASL (Hot Air Solder Leveling), ENIG (Electroless Nickel Immersion Gold), OSP (Organic Solderability Preservative), Immersion Silver, and Immersion Tin. HASL is a method in which the copper pattern is immersed in molten solder and excess solder is removed with hot air; while it is inexpensive, the surface may not be flat. ENIG is a method of immersing gold after chemical nickel plating; it is widely used in high-end products because it produces a flat surface, excellent solderability, and allows for long-term storage. The nickel layer is generally formed with a thickness of 3-6 µm, and a gold layer with a thickness of 0.05-0.15 µm is formed on top of it. Nickel acts as a diffusion barrier for copper, while gold prevents the oxidation of nickel and provides excellent solderability. OSP is a method of preventing oxidation by coating an organic compound onto a copper surface; it is environmentally friendly and inexpensive, but has a short shelf life. Generally, organic compounds of the imidazole or benzotriazole family are used for OSP. Immersion silver is a method of immersion plating silver onto a copper surface; it offers excellent solderability, a flat surface, and a moderate cost. The thickness of the silver layer is typically 0.1–0.3 µm, providing excellent electrical and thermal conductivity. Immersion tin is a method of immersion plating tin onto a copper surface; it is suitable for lead-free processes and is inexpensive. The thickness of the tin layer is typically 0.8–1.2 µm. In the embodiments of the present invention, ENIG surface treatment was applied to ensure stable solderability and long-term reliability.
[0066] A plurality of LEDs (150, 160) are mounted on the copper pattern layers (130, 140), respectively. The LEDs (150) on the upper surface and the LEDs (160) on the lower surface are core components of the present invention, and their arrangement structure and characteristics determine the performance of the double-sided transparent display. An LED (Light Emitting Diode) is a semiconductor device that is an electro-optical conversion device that emits light when current is applied, and its light emission principle is that energy emitted during electron-hole recombination at a pn junction is converted into photons. The brightness of the LED is controlled according to the applied voltage and current, and the color is determined by the bandgap energy of the semiconductor material used. Red LEDs generally use AlGaInP (Aluminum Gallium Indium Phosphide) material with a wavelength of about 620-640 nm, green LEDs use InGaN (Indium Gallium Nitride) material with a wavelength of about 520-530 nm, and blue LEDs use InGaN material with a wavelength of about 460-470 nm.
[0067] The LED (150, 160) used in the present invention is generally a Surface Mount Device (SMD) type LED package. SMD LEDs have electrode pads formed on the bottom of the package without lead wires, allowing for direct surface mounting on a substrate, which is advantageous for miniaturization and automated production. Although the size of the LED package varies depending on the application, for display applications, small packages with a size of 1.0mm x 1.0mm to 3.0mm x 3.0mm are generally used. To achieve a finer pixel pitch, micro LEDs of 0.5mm x 0.5mm or smaller may also be used. An LED chip is mounted inside the package and connected to the electrodes via wire bonding or a flip-chip method. Wire bonding is a method of connecting the electrode pads of the LED chip to the leads of the package using gold (Au) or aluminum (Al) wires, while flip-chip is a method of directly bonding the LED chip to the package substrate by flipping it over, which has a short electrical path and excellent heat dissipation. To protect the LED chip and increase light extraction efficiency, it is encapsulated with a transparent epoxy resin or silicone resin, and color conversion is implemented using a resin mixed with a phosphor as needed.
[0068] It is desirable that the LEDs (150, 160) on the top and bottom surfaces be configured as RGB LED packages to realize full-color images. An RGB LED package is a package in which three LED chips of red, green, and blue are integrated, and various colors can be expressed by individually adjusting the brightness of each color. In the RGB color space, if each color is controlled in 0-255 steps (8 bits), approximately 16.7 million (256³) colors can be realized, which is the standard for full-color displays. Methods of implementing RGB LED packages include the discrete method, in which three LED chips are placed side by side within a single package, and the phosphor conversion method, in which red and green phosphors are placed on top of the blue LED; the former is advantageous in terms of color purity and control precision and is mainly used in high-end displays. In the discrete RGB method, since each color LED chip is controlled independently, a wide color gamut can be provided, and white balance adjustment is easy.
[0069] The brightness of the LEDs (150, 160) is expressed in units of nits (cd / m²), which represent the luminous intensity per unit area. In the present invention, the pixel pitch between the LEDs is 4 mm or less, and due to the heat dissipation characteristics of the metal core substrate (100), substrate deformation and pixel coordinate changes caused by heat generated during LED driving are suppressed, making it possible to stably achieve high brightness of 5000 nits or more while maintaining transparency through the transparent area (170). High brightness of 5000 nits or more is a level that ensures sufficient visibility even in outdoor environments. Compared to typical indoor displays requiring 300-500 nits and outdoor displays requiring 5000-10000 nits, it can be seen that the display of the present invention can be used for both indoor and outdoor purposes. To achieve high brightness, a high current must be applied to the LEDs, which causes a rapid increase in heat generation. Generally, the luminous efficiency of an LED is at the level of 100-150 lm / W, and the remaining energy is released as heat. For example, an LED consuming 1W of power generates about 0.6-0.8W of heat, so displays with hundreds of densely packed LEDs generate significant heat. Since LED efficiency has a characteristic called thermal droop, which decreases as temperature rises, effective thermal management is key to driving high brightness.
[0070] To solve this heat generation problem, the present invention utilizes the excellent heat dissipation characteristics of a metal core substrate (100). Heat generated from the LED (150, 160) is transferred to the copper pattern layer (130, 140) through the solder joint and then transferred to the metal core substrate (100) via the insulating layer (110, 120). Since the metal core substrate (100) has high thermal conductivity, it rapidly diffuses heat and disperses it over the entire surface area. The dispersed heat is released into the surrounding air through natural convection and radiation from the surface of the metal core substrate (100). Natural convection is heat transfer caused by natural air circulation in which heated air rises and cooled air descends, and radiation is a phenomenon in which heat is transferred in the form of electromagnetic waves. Through this heat dissipation mechanism, substrate deformation and pixel coordinate changes caused by heat generated during LED operation are suppressed, making it possible to stably achieve high brightness of 5000 nit or more while maintaining transparency through the transparent area (170).
[0071] Substrate deformation and pixel coordinate changes are explained in detail. When a display substrate is heated, thermal expansion occurs; the greater the coefficient of thermal expansion (CTE) of the material, the greater the amount of deformation. Polymer materials such as PET have a very high CTE of approximately 30–70 ppm / °C, so a 1m-long substrate expands by about 1.5–3.5mm when the temperature rises by 50 degrees Celsius. This deformation makes it difficult to maintain the precise positioning of pixels, and the impact is even more pronounced, especially at fine pixel pitches where the spacing between pixels is narrow. On the other hand, the CTE of aluminum is approximately 23 ppm / °C, which is about one-third the level of PET. Furthermore, due to aluminum's high thermal conductivity, the temperature of the entire substrate remains uniform, preventing localized deformation. A small temperature gradient minimizes differential expansion, which can prevent warping or bending. This thermal stability is an essential factor for outdoor displays that operate at high brightness for extended periods.
[0072] With reference to FIGS. 2 and 3, the arrangement structure of the LEDs (150, 160) is described in detail. The LEDs (150) on the upper surface are arranged in a first grid pattern, and the LEDs (160) on the lower surface are arranged in a second grid pattern positioned between the grid areas of the first grid pattern. Here, a grid pattern refers to a matrix structure in which LEDs are arranged in regular rows and columns, and a square or rectangular grid is generally used. The first grid pattern is a pattern in which the LEDs (150) on the upper surface are arranged at regular intervals, and the second grid pattern has the same period as the first grid pattern but is arranged with an offset position.
[0073] Looking at the top LED (150) indicated by a solid line and the bottom LED (160) and transparent area (170) indicated by a dotted line in FIG. 2, it can be seen that the bottom LED (160) is positioned at the center of the grid area where the top LED (150) is not placed, and the transparent area (170) is regularly arranged in between. This arrangement is called a staggered arrangement or offset arrangement and has a structure similar to the black and white arrangement of a chessboard. The advantage of the staggered arrangement is that pixel density can be effectively utilized when displaying images independently on the front and back sides, respectively. If the top and bottom LEDs are placed in the same position, two LEDs are vertically overlapped in the same area of the metal core substrate (100), which is structurally inefficient and disadvantageous for heat dissipation. On the other hand, using the staggered arrangement allows for efficient utilization of the area of the metal core substrate (100) while ensuring uniform pixel density on each side. In addition, direct light overlap can be effectively prevented by the above staggered arrangement, and the transparent area (170) can be maximized.
[0074] FIG. 3 is a front view of the grid arrangement structure of a double-sided LED, clearly showing that the upper LED (150) and the lower LED (160) do not overlap when projected vertically. The projection line (y1) drawn vertically from the center of the upper LED (150) and the projection line (y2) drawn vertically from the center of the lower LED (160) are at different positions, which means that the two LEDs do not overlap in the vertical direction. This non-overlapping arrangement requires precise alignment in the manufacturing process and is implemented using a vision system in the SMT process described later. Through the non-overlapping arrangement, optical interference between the double-sided LEDs can be minimized, and light transmission through the transparent area (170) can be maximized.
[0075] With reference to FIG. 4, the structure for limiting the light emission angle of the LEDs is described in detail. The light emission angle of the LEDs (150, 160) is limited to block optical interference between the light emission of one side of the LED and the light emission of the other side, and directional light emission control is performed so that the front LED (150) emits light only in the forward direction and the rear LED (160) emits light only in the rear direction. The light emission angle limitation is implemented by lenses (151, 161) included in the LED package. The lens (151) placed on the upper LED (150) focuses the light generated from the LED chip forward (upper direction), and in this process, the wide angle is limited to a1. Similarly, the lens (161) placed on the lower LED (160) focuses the light downward (lower direction) and limits the wide angle to a2. It is preferable that the wide angles a1 and a2 are each in the range of 60 to 100 degrees.
[0076] The principle of limiting the emission angle can be explained optically as follows. The LED chip itself generally has a Lambertian emission pattern, which has maximum brightness in the frontal direction, and as the angle increases, the cosine law (L( It is a characteristic in which brightness decreases according to ) = L0 × cos(θ)). The half-angle of the Lambertian light source is very wide, approximately 120 degrees, so the light spreads in all directions. While such a wide emission angle is advantageous for lighting purposes, it becomes a problem in double-sided displays like the present invention. If the light from the upper LED (150) spreads widely and exits to the side of the substrate, the light can go around the edge of the metal core substrate (100) and reach the lower LED (160) area, which causes interference with the image displayed on the lower surface.
[0077] To prevent this, a lens (151, 161) is used to limit the light emission angle. The lens is typically included as part of the LED package and is molded from transparent epoxy resin, silicone resin, or polycarbonate (PC). The shape of the lens can be a convex lens, a concave lens, a TIR (Total Internal Reflection) lens, or a free-form surface shape, and is optimized using optical simulation software (e.g., Zemax, LightTools, TracePro) to obtain the desired light distribution. A light emission angle of 60-100 degrees is generally classified as a medium-angle lens, which is a suitable range for direct-view displays. If the light emission angle is too narrow (e.g., 30 degrees or less), the viewing angle is limited so that the screen can only be viewed from the front, and if it is too wide (e.g., 120 degrees or more), interference between the two sides may occur; therefore, 60-100 degrees is a range that balances the viewing angle and interference prevention.
[0078] An additional function of the lens (151, 161) is to improve light extraction efficiency. When light generated from an LED chip exits from the semiconductor into the air, total internal reflection may occur due to the difference in refractive index, which causes some of the light to be trapped inside the chip instead of being emitted to the outside. According to Snell's law, total internal reflection occurs when the angle of incidence exceeds the critical angle, and the critical angle is determined by the refractive indices of the two media. For example, when light exits from GaN (refractive index approximately 2.4) into air (refractive index 1.0), the critical angle is approximately 25 degrees; therefore, light incident at an angle greater than this is totally reflected and cannot exit to the outside. Since the lens has an intermediate refractive index (epoxy resin approximately 1.5, silicon resin approximately 1.4), it mitigates the difference in refractive index between the semiconductor (refractive index approximately 2.4-3.5) and the air (refractive index 1.0), thereby increasing light extraction efficiency. In addition, the curvature of the lens changes the total reflection angle, inducing more light to be emitted forward. Light extraction efficiency can be improved by 30-50% through lens shape optimization.
[0079] When the light blocking function of the metal core substrate (100) is combined with the light emission angle limitation, optical interference between the two sides is virtually eliminated. As can be seen in FIG. 4, light generated from the upper LED (150) is focused upward by the lens (151), and light spreading to some sides is also blocked by the metal core substrate (100) so that it does not reach the lower LED (160) area. This contributes significantly to increasing the contrast ratio and color purity of the image displayed on each side. The contrast ratio is defined as the ratio of maximum brightness to minimum brightness, and without interference between the two sides, the minimum brightness (black level) can be kept low, thereby achieving a high contrast ratio. Generally, a contrast ratio of 1000:1 or higher is considered a high-quality display, and this can be sufficiently achieved through the structure of the present invention.
[0080] As an additional embodiment of the present invention, a light-blocking structure may be further placed around the LEDs (150, 160). The light-blocking structure may be composed of black resin or metal barriers and is placed in the space between the LEDs to prevent light crosstalk between adjacent LEDs. The black resin is generally formed from epoxy or silicone resin mixed with carbon black and absorbs light to minimize reflection. The metal barriers may be made of aluminum or stainless steel and physically block light. This is particularly useful at fine pixel pitches, as the closer the distance between LEDs, the higher the likelihood of light mixing between adjacent pixels. The light-blocking structure may be formed by screen printing, dispensing, or precision die forming methods, and its height is set to be similar to or slightly lower than the height of the LEDs to block lateral leakage of light.
[0081] FIG. 5 is a cross-sectional view showing the detailed stacked structure of an MCPCB substrate according to the present invention and a structure in which an optical adhesive layer and transparent glass are attached to a transparent region (170). Referring to FIG. 5, the central metal core substrate (100) is formed of aluminum material, has a thickness of 1.0 mm, and has a thermal conductivity of 205 W / mK. Insulating layers (110, 120) are formed on the upper and lower surfaces, respectively, and the insulating layers (110, 120) are made of alumina (Al) in epoxy resin. It is formed from a composite material containing O₃, boron nitride (BN), and aluminum nitride (AlN), has a thickness of 100 μm, a thermal conductivity of 2.0 W / mK, and an dielectric breakdown voltage of 2-4 kV. Copper pattern layers (130, 140) are formed on the insulating layers (110, 120), and the copper pattern layers (130, 140) are formed from a copper foil (1 oz) with a thickness of 35 μm. An LED package (150, 160) is mounted on the copper pattern layers (130, 140).
[0082] As an important feature of the present invention, an optical adhesive layer (OCA) (171) maintaining a transmittance of 60% or more is formed on the transparent area (170), and a transparent glass (172) is attached on the optical adhesive layer (171) to simultaneously secure mechanical strength and transparency. As can be seen in FIG. 5, the transparent area (170) is an open space where the metal core substrate (100), insulating layer (110, 120), and copper pattern layer (130, 140) are not formed, and the optical adhesive layer (171) is filled in this space, and a transparent glass (172) is disposed on the upper and lower surfaces thereof.
[0083] The optical adhesive layer (171) protects the transparent area (170), provides mechanical strength, and serves to attach the transparent glass (172). Various types of materials can be used for the optical adhesive layer, and the characteristics of each are as follows.
[0084] First, Optically Clear Adhesive (OCA) films can be used. OCA films are transparent acrylic-based adhesive films with adhesive strength on both sides, and are generally supplied in thicknesses ranging from 25 µm to 250 µm. The main features of OCA films are high light transmittance (generally over 90%), excellent adhesion, reworkability, and minimized bubble formation. OCA films are supplied in roll form and can be attached using lamination equipment, making them suitable for mass production. The adhesion mechanism of OCA films is pressure-sensitive; when external pressure is applied, the adhesive material fills the fine irregularities on the surface of the substrate, bonding through van der Waals forces. OCA films do not require a curing process, making the manufacturing process simple, and allow for immediate bonding at room temperature. Representative OCA film products include 3M's 8146 series and Mitsui Chemical's MHM series.
[0085] Second, liquid optically clear resin (OCR) can be used. OCR is a transparent resin in a liquid state that is filled into a transparent area (170) and then solidified through UV curing or heat curing. The main features of OCR are that it can be completely filled even in complex shapes, bubble removal is easy, high light transmittance (generally 92% or more), and excellent adhesion. Materials that can be used as OCR include epoxy resin, silicone resin, and urethane acrylate resin. Epoxy OCR provides excellent adhesion and chemical resistance, but because of the possibility of yellowing, a UV blocker must be added. Silicone OCR has excellent heat resistance and weather resistance, is easy to adjust the refractive index, and does not yellow, but its adhesion is relatively low. Urethane acrylate OCR enables rapid UV curing and has excellent flexibility, but it may have a high water absorption rate. OCR is applied by a dispensing method, then undergoes a degassing process in a vacuum chamber to remove bubbles, and is cured by UV or heat. In the case of UV-curing OCR, it is generally cured by irradiating with a UV-LED of 365nm or 395nm wavelength for several seconds to minutes. In the case of thermo-curing OCR, it is cured by heating at 80-150 degrees Celsius for 30 minutes to 2 hours.
[0086] Third, a transparent adhesive in the form of a sealant can be used. The sealant is applied only to the edges of the transparent area (170) to fix the transparent glass (172), while the central part is filled with air. This method minimizes material usage and is advantageous for lightweighting, but an air layer exists between the transparent glass (172) and the LEDs (150, 160), which may cause reflection due to the difference in refractive index. Since the refractive index of air is approximately 1.0 and the refractive index of glass is approximately 1.5, a reflection loss of about 4% occurs at the interface. To compensate for this, an anti-reflection coating can be applied. Silicone sealants, urethane sealants, butyl sealants, etc., can be used as sealants, and each has different characteristics such as heat resistance, adhesion, and water resistance.
[0087] Fourth, photocurable acrylic adhesives can be used. These are mixtures of acrylic monomers and photoinitiators, which cure through radical polymerization upon UV irradiation. Photocurable acrylic adhesives have the advantages of fast curing speed (within seconds), room temperature curing, low curing shrinkage, and excellent transparency. However, since curing may be difficult in shadow areas where UV cannot penetrate, a two-stage curing system (UV curing + heat curing or moisture curing) is sometimes used.
[0088] Fifth, low melting glass or glass frit may be used. This is a method of bonding by applying glass powder that softens at 400-600 degrees Celsius in paste form and then heating it. Low melting glass bonding provides very strong adhesion and excellent hermetic seal, and is stable even in high-temperature environments. However, since a high-temperature process is required, it is difficult to apply after LEDs or other temperature-sensitive components have been mounted, and it is preferable to use it before attaching the transparent glass (172).
[0089] Sixth, Liquid Silicone Rubber (LSR) can be used. LSR is a two-component silicone that is heat-cured after mixing. The characteristics of LSR include maintaining flexibility over a wide temperature range (-60°C to 200°C), excellent weather and chemical resistance, high light transmittance (generally over 90%), and biocompatibility. LSR is cured at 120–180°C for minutes to tens of minutes, and it retains flexibility even after curing, which can relieve stress caused by differences in thermal expansion. Compared to general rubber, LSR has higher mechanical strength and a smaller compression set, resulting in excellent long-term reliability.
[0090] In a preferred embodiment of the present invention, as shown in FIG. 5, a method is used to completely fill the transparent area (170) by filling the liquid optically transparent resin (OCR) (171) into the transparent area (170) and UV curing it. This method has the advantages of being able to completely fill even complex shapes of the transparent area (170), minimizing bubble formation, having excellent adhesion to transparent glass (172), and stably securing a light transmittance of 60% or more. However, depending on the embodiment, other materials mentioned above may also be selectively used, and can be selected according to the application field by considering the characteristics of each material.
[0091] It is important to maintain a transmittance of 60% or more for the optical adhesive layer (171) to ensure practicality as a transparent display. Transmittance is defined as the ratio of transmitted light to incident light and is expressed as a percentage. Since transmittance is reduced by absorption, reflection, and scattering of the material, the optical adhesive layer (171) must be designed to minimize these losses. Generally, the transmittance of the optical adhesive layer (171) is measured at a wavelength of 550 nm (the center wavelength of visible light), and the present invention aims for a transmittance of 60% or more, preferably 80% or more, and more preferably 90% or more. To improve transmittance, the purity of the material must be increased, yellowing must be prevented, the refractive index must be matched to that of glass, and bubbles or foreign substances must be prevented.
[0092] The transparent glass (172) provides mechanical strength and serves to protect the display from the external environment. As the transparent glass (172), soda-lime glass, borosilicate glass, tempered glass, chemically strengthened glass, etc., may be used. Soda-lime glass is the most common and economical glass, has a transmittance of about 90%, and is widely used in general construction and home appliances. Borosilicate glass is made of boron oxide (B Containing O₃, it has a low coefficient of thermal expansion and is resistant to thermal shock, making it suitable for use in laboratory equipment and cooking utensils. Tempered glass is produced by heating glass to a high temperature and then rapidly cooling it to create compressive stress on the surface; it has 3 to 5 times higher mechanical strength than ordinary glass and is safe because it shatters into small particles upon breakage. Chemically strengthened glass is produced by immersing glass in a molten salt bath (typically a potassium nitrate solution) to create compressive stress by replacing sodium ions on the surface with potassium ions; it can be manufactured thinner than tempered glass (0.5-2 mm) and has excellent flatness, making it widely used as display cover glass. Representative examples of chemically strengthened glass include Corning's Gorilla Glass and AGC's Dragontrail.
[0093] The thickness of the transparent glass (172) is generally selected in the range of 0.5 mm to 6 mm and varies depending on the application. Thin glass (0.5-2 mm) is suitable for mobile devices or small displays and is advantageous for lightweighting but has a high risk of breakage. Medium-thickness glass (2-4 mm) is suitable for indoor displays or home appliances and has a good balance of strength and weight. Thick glass (4-6 mm) is suitable for outdoor displays or large installations and provides excellent strength but becomes heavy. In the embodiment of the present invention, 2 mm of chemically strengthened glass or 3 mm of tempered glass was used to ensure sufficient strength and transparency.
[0094] An additional functional coating may be applied to the surface of the transparent glass (172). An anti-reflective coating (AR coating) is a coating that increases transmittance by reducing reflection on the glass surface, and is generally a multilayer thin film structure (MgF₂). It is formed from a combination of materials such as SiO₂, TiO₂, etc., and can reduce reflectivity to less than 1%. Anti-fingerprint coating (AF coating) is a coating that uses fluorine compounds to make the glass surface hydrophobic, preventing fingerprints or contaminants from adhering. Anti-smudge coating is similar to AF coating but provides greater durability. Hard coating is a coating that improves the scratch resistance of the glass surface and is generally formed from silicon oxycarbide (SiOC) or diamond-like carbon (DLC). UV blocking coating is a coating that blocks ultraviolet rays to prevent yellowing or deterioration of internal components.
[0095] In this stacked structure, the flow of heat can be quantitatively analyzed. Heat generated from the LED is first transferred to the copper pattern layer (130 or 140) through the solder joint. The thermal resistance of the solder joint is generally about 1-5 K / W. Since the thermal conductivity of the copper pattern layer in the area direction is very high at about 398 W / mK, heat diffuses rapidly, and heat is also transferred to the insulating layer (110 or 120) in the thickness direction. Since the thermal conductivity of the insulating layer is 2.0 W / mK and the thickness is 100 μm, the thermal resistance per unit area is about 0.05 K·m² / W. Since the thermal conductivity of the metal core substrate (100) is 205 W / mK and the thickness is 1.0 mm, the thermal resistance per unit area is about 0.0049 K·m² / W, which is much lower than that of the insulating layer. Therefore, the total thermal resistance is mainly determined by the insulating layer, and the role of the metal core substrate (100) is to disperse the absorbed heat over a wide area and finally release it to the outside through convection and radiation.
[0096] According to the embodiment, heat sink fins may be additionally attached to the surface of the metal core substrate (100), or a cooling fan may be installed to induce forced convection. Heat sink fins improve convective heat transfer by increasing the surface area, and generally, extruded aluminum profiles are used. The shapes of the heat sink fins include plate fins, fin fins, and louver fins, each having different heat transfer characteristics. Plate fins are simple to manufacture and have low resistance but a relatively low heat transfer coefficient; fin fins have a large surface area but high air resistance; and louver fins have a high heat transfer coefficient but are complex to manufacture. The cooling fan increases the airflow to increase the convective heat transfer coefficient; while the heat transfer coefficient of natural convection is about 5-25 W / (m²·K), forced convection can be improved by more than 10 times to 25-250 W / (m²·K). Types of cooling fans include axial fans, centrifugal fans, and cross-flow fans, each having different flow-pressure characteristics. These additional cooling means may be required for ultra-high brightness displays (10,000 nits or more) or displays installed in enclosed spaces.
[0097] The display of the present invention can be applied to various installation locations. Outdoor transparent advertising displays are installed on building exterior glass windows, bus stop glass partitions, shop windows, etc., to display advertising videos on both sides while allowing the background or products behind them to be visible, thereby providing advertising effects while maintaining a sense of visual openness. Transparent information displays at airports and subway stations convey operational information, timetables, and announcements to passengers; they are installed on glass partitions in the center of platforms, allowing them to be viewed from both sides while keeping the opposite side transparent. Glass partition displays in shopping malls display different advertisements on both sides to enhance store promotion, while maintaining a sense of space by allowing customers to see the area beyond the partition. In exhibitions or museums, transparent displays can be installed in glass display cases to protect artworks or exhibits while simultaneously providing information. As an architectural media facade, it is integrated into the curtain wall glass of a building exterior, functioning as a transparent window during the day and a large media facade at night. As a car windshield display, a transparent display can be integrated into the front windshield to display AR (Augmented Reality) navigation information. In these various applications, the MCPCB-based double-sided transparent LED display of the present invention provides excellent heat dissipation performance, high brightness, stable pixel precision, and transparency of more than 60%, enabling reliable image display.
[0098] With reference to FIG. 6, a method for manufacturing a high-brightness double-sided transparent LED display on an MCPCB substrate according to the present invention will be described in detail. The manufacturing method comprises: a step of preparing a metal core substrate made of aluminum material, wherein the LED mounting area is patterned and designed so that the transparent area occupies 60% or more of the total area; a step of forming an insulating layer on an upper surface and a lower surface corresponding to the LED mounting area of the metal core substrate; a step of forming a copper pattern layer on the insulating layer (S10); a step of mounting a plurality of LEDs in a first grid pattern on the copper pattern layer on the upper surface using an SMT process (S20); a step of flipping the substrate (S30); a step of mounting a plurality of LEDs in a second grid pattern on the copper pattern layer on the lower surface using an SMT process so as to be positioned between the grid areas of the first grid pattern (S40); and a step of completing a transparent double-sided display through this (S50).
[0099] First, in step S10, a metal core substrate (100) made of aluminum material is prepared, and an LED mounting area is designed by patterning the LED mounting area so that the transparent area (170) occupies more than 60% of the total area; an insulating layer (110, 120) is formed on the upper and lower surfaces corresponding to the LED mounting area of the metal core substrate (100); and a copper pattern layer (130, 140) is formed on the insulating layer (110, 120).
[0100] The preparation and patterning design of the metal core substrate (100) will be described in detail. An aluminum plate to be used as the metal core substrate (100) is prepared. As previously described, the aluminum plate is selected from alloys such as 3003, 5052, and 6061, and the surface is flattened through chemical or mechanical polishing. Surface roughness is generally managed to Ra 0.5 μm or less to improve adhesion with the insulating layer in subsequent processes. Surface flatness is evaluated using an optical profilometer or a stylus-type surface roughness measuring instrument. In some embodiments, anodizing may be performed on the surface to form a thin aluminum oxide layer, which contributes to corrosion prevention and improved insulation. Anodizing is a process in which aluminum is used as the anode to perform electrolysis in an electrolyte solution (generally a sulfuric acid or chromic acid solution), forming a porous aluminum oxide layer on the surface. The thickness of the anodized layer is generally 5-25 μm, and coloring treatment may be performed as needed.
[0101] In the patterning design stage, Computer-Aided Design (CAD) software is used to design the arrangement of the LED mounting area and the transparent area (170). The considerations for the design are as follows. First, the size and arrangement of the LED mounting area are optimized so that the transparent area (170) occupies at least 60% of the total area. Second, the upper LED (150) and the lower LED (160) are arranged in an alternating pattern, and the coordinates are calculated precisely so that they do not overlap during vertical projection. Third, the shape of the metal core substrate (100) is determined by considering the wiring path of the copper pattern layers (130, 140). Fourth, the minimum bridge width of the metal core substrate (100) is set to ensure mechanical strength. Generally, the minimum bridge width of the metal core substrate (100) connecting the LED mounting areas is preferably 0.5 mm or more. Fifth, the minimum feature size of the pattern is determined by considering the feasibility of the manufacturing process. In the case of laser cutting, feature sizes of 0.1mm or larger are generally possible.
[0102] Once the design is complete, the metal core substrate (100) is patterned using the patterning process (laser cutting, CNC milling, chemical etching, etc.) described above. In an embodiment of the present invention, the metal core substrate (100) is patterned using fiber laser cutting. Laser cutting conditions are controlled by laser output, feed rate, focal position, type of assist gas, and pressure. For aluminum, a laser output of 1-3 kW, a feed rate of 1-5 m / min, and nitrogen or air are generally used as the assist gas. The assist gas serves to remove molten metal and prevent oxidation. After laser cutting, a burr removal and edge finishing process is performed to remove sharp edges and improve surface quality. At this time, the method for forming the transparent area (170) is described as above.
[0103] An insulating layer (110, 120) is formed in the LED mounting area of a patterned metal core substrate (100). The formation of the insulating layer (110, 120) is performed using the prepreg method described above. A slurry is prepared by mixing an epoxy resin and a ceramic filler (alumina, boron nitride, aluminum nitride). The slurry is adjusted by adding a solvent to ensure it has an appropriate viscosity, and a ball mill, three-roll mill, or ultrasonic treatment is performed to disperse the filler. After impregnating the slurry into a glass fiber cloth or polyester film, it is dried at 80-100 degrees Celsius to produce a prepreg in a semi-cured state (B-stage). The B-stage is an intermediate cured state of the thermosetting resin, in which the solvent has been removed but it is not completely cured, so it has adhesiveness and its fluidity is restored upon heating. The prepreg is placed precisely aligned on the upper and lower surfaces of the LED mounting area of the metal core substrate (100). At this time, care must be taken not to place prepreg in the transparent area (170). An optical alignment system or a mechanical jig may be used for alignment.
[0104] Lamination is performed using a vacuum laminator under conditions of 150-180 degrees Celsius and 10-50 bar. A vacuum environment (generally 1 torr or less) prevents the formation of bubbles, thereby improving adhesion quality. During the lamination process, the prepreg flows to fill the fine irregularities on the surface of the metal core substrate (100) and is partially cured and bonded by heat and pressure. After lamination, final curing is performed at 150-180 degrees Celsius for 1-2 hours to complete the insulating layer (110, 120). During curing, the temperature and time are precisely controlled to minimize residual stress and ensure dimensional stability. After curing, the quality of the insulating layer (110, 120) is inspected, and inspection items include thickness uniformity, surface flatness, presence of bubbles, and adhesion strength.
[0105] A copper pattern layer (130, 140) is formed on an insulating layer (110, 120). The process of forming the copper pattern layer (130, 140) proceeds in the same manner as previously described. First, a copper foil with a thickness of 35 μm is laminated onto the insulating layer (110, 120). The lamination of the copper foil is performed by activating the adhesive through the application of heat and pressure, and an epoxy-based or acrylic-based adhesive is used. The lamination temperature is generally 120-160 degrees Celsius, and the pressure is 5-20 bar. Next, a photoresist is applied to the surface of the copper foil. The photoresist may be of a negative or positive type, and is applied by spin coating or roll coating of liquid photoresist, or by laminating dry film photoresist. The coating thickness is generally 20-50 μm.
[0106] A photomask with a circuit pattern is placed in close contact with a photoresist, and UV light is irradiated to perform exposure. The photomask is made of quartz glass or soda-lime glass with a chromium (Cr) pattern formed on it, and quartz glass is used for high-resolution patterns. The exposure energy is adjusted according to the type of photoresist and is generally 100–300 mJ / cm². Contact aligners, proximity aligners, or projection aligners are used as exposure equipment. Contact aligners expose by bringing the mask and substrate into close contact, resulting in high resolution but a risk of mask damage. Proximity aligners expose by maintaining a small gap (10–50 µm) between the mask and the substrate, which prevents mask damage but results in a decrease in resolution due to diffraction. Projection aligners project the mask pattern onto the substrate through an optical system, so there is no mask damage and reduction projection is possible, but the equipment is expensive.
[0107] After exposure, development is performed using a developer. The developer is generally sodium carbonate (Na₂S) A weakly alkaline aqueous solution of CO₃ or sodium hydroxide (NaOH) is used, with a concentration of 1–3 wt%. Development methods include dipping, spraying, or paddle methods. The spraying method involves spraying the developer onto the substrate; it offers fast development speed and excellent uniformity. After development, the substrate is washed with pure water to remove any residual developer.
[0108] Subsequently, the unprotected copper is removed through an etching process. Aqueous solutions of ferric chloride (FeCl3) or ammonium persulfate ((NH4)2S2O8) are used as etching solutions. The chemical reaction equation for ferric chloride etching is 2FeCl3 + Cu → 2FeCl2 + CuCl2. Etching conditions are controlled by solution concentration, temperature, stirring speed, and spray pressure. Generally, ferric chloride etching is performed at 40–50°C and a concentration of 30–45 °Bι (Baumé degree, an indicator of specific gravity), with an etching rate of approximately 25–40 µm / min. The chemical reaction equation for ammonium persulfate etching is (NH4)2S2O8 + Cu → (NH4)2SO4 + CuSO4. Ammonium persulfate etching is performed at 40–50°C and a concentration of 150–250 g / L, with an etching rate of approximately 20–30 µm / min. Immersion, spray, or conveyor methods are used for etching. Spray etching is a method of etching by spraying the etching solution at high pressure, which offers a fast etching rate and minimizes side etching (undercut). After etching, the surface is thoroughly washed with pure water to remove residual etching solution and copper ions.
[0109] After etching, the residual photoresist is stripped. An aqueous sodium hydroxide solution (concentration 3-5 wt%) is generally used as the stripping solution, and the process is carried out by immersion or spraying at 40-60 degrees Celsius. After stripping, the copper pattern layer (130, 140) is washed with pure water and dried to obtain the final copper pattern layer (130, 140). The quality of the copper pattern layer (130, 140) is inspected, and inspection items include line width / spacing accuracy, presence of open / short circuits, etching profile (verticality), surface cleanliness, etc.
[0110] Surface treatment is performed on the surface of the copper pattern layer (130, 140). In an embodiment of the present invention, ENIG (Electroless Nickel Immersion Gold) surface treatment is applied. The ENIG process proceeds as follows. First, contaminants and oxide films are removed from the copper surface by degreasing and acid cleaning. Degreasing is generally performed at 50-70 degrees Celsius using an alkaline degreasing agent, and acid cleaning is performed using sulfuric acid (H₂ This is performed at room temperature using a 10-20 wt% aqueous solution of SO₄. Next, electroless nickel plating is carried out. Electroless nickel plating is a plating method utilizing a chemical reduction reaction, which reduces nickel ions to metallic nickel without an external power source. The composition of the electroless nickel plating solution generally consists of nickel ions (NiSO₄ or NiCl₂) and a reducing agent (sodium hypophosphite NaH₂). It consists of PO₂, a complexing agent (citric acid or lactic acid), and a pH adjuster (sodium hydroxide or ammonia). Plating is performed at 80–90°C and a pH of 4.5–5.5, with a plating speed of approximately 10–20 µm / hr. The target thickness of the nickel layer is 3–6 µm. After nickel plating, immersion gold plating is performed. Immersion gold plating is a plating method utilizing a substitution reaction, in which nickel atoms on the nickel surface are replaced by gold ions to form a gold layer. The composition of the immersion gold plating solution generally consists of gold ions (gold cyanide or gold sulfite), a complexing agent, and a pH adjuster. Plating is performed at 80–90°C and a pH of 4.5–5.5, with a plating time of 5–20 minutes. The target thickness of the gold layer is 0.05–0.15 µm. After ENIG treatment, it is washed with pure water and dried.
[0111] In step S20, a plurality of LEDs (150) are mounted in a first grid pattern on the copper pattern layer (130) of the upper surface using an SMT process. The SMT process is Surface Mount Technology, an automated process for directly mounting lead-free electronic components onto the surface of a substrate. The detailed steps of the SMT process are as follows. First, solder paste is printed at the LED mounting location on the copper pattern layer (130). Solder paste is a viscous material mixed with fine solder powder (generally 20-50 μm) and flux, and is applied using a screen printing method with a stencil. The solder powder is generally a lead-free solder alloy (Sn-Ag-Cu, SAC305, etc.), and the particle size distribution and shape affect the printing quality. Flux serves to remove the oxide film and improve wettability during soldering, and there are rosin type, water-soluble type, and no-clean type. A stencil is a metal plate (typically stainless steel) produced by laser cutting or chemical etching, with openings at the locations of LED pads. The thickness of the stencil is typically 100–150 µm, which determines the printing thickness of the solder paste. The stencil is aligned with the substrate, and the solder paste is pushed in with a squeegee to fill the openings. The squeegee is made of metal, rubber, or polyurethane, and its hardness and angle affect the print quality. After printing, the stencil is removed, leaving solder paste on the pads.
[0112] Next, the LED (150) is placed at the location where the solder paste is printed. This is performed using automated equipment called a pick-and-place machine, where a vacuum nozzle picks up the LED and places it at the correct position. The pick-and-place machine receives the LED from a feeder, recognizes the position of the LED and the substrate using a vision system, and places it through precise motion control. Placement precision is generally ±25 µm or less, and the latest equipment achieves precision of ±10 µm. The placement of the LED is performed according to a first grid pattern, and the position of each LED is based on pre-programmed coordinate data. The coordinate data is extracted from a CAD file and is provided in a Gerber file or ODB++ format. It is important to accurately match the polarity of the LED during placement, and the vision system recognizes the marking on the LED package to verify the orientation.
[0113] Once the placement of all LEDs (150) is complete, the solder paste is melted by heating in a reflow oven. The temperature profile is important for the reflow process and generally consists of four stages: preheat, activation, reflow, and cooling. In the preheating stage, the substrate is gradually heated to prevent thermal shock and activate the flux, and the temperature is maintained at approximately 150-180 degrees Celsius. The ramp rate is generally controlled at 1-3°C / s. The length of the preheating stage is 60-120 seconds, which ensures that the entire substrate is heated uniformly. In the activation stage, the flux removes the oxide film on the copper surface to improve wettability, and the temperature is maintained at approximately 180-200 degrees Celsius. This stage is also called the soaking zone and is maintained for 60-120 seconds. During the reflow stage, the solder melts to form a metal bond between the copper pad and the LED electrode, reaching a temperature of over 185°C, which is above the melting point of lead-free solder, with a peak temperature of 230–250°C. Since the melting point of SAC305 lead-free solder is approximately 217°C, the peak temperature is set 20–30°C higher than the melting point. The time above liquidus (TAL) at the peak temperature is 30–90 seconds, during which the solder completely melts to form a uniform alloy layer. If the TAL is too short, an incomplete bond is formed, while if it is too long, the LED or substrate may suffer thermal damage. During the cooling stage, the substrate is slowly cooled to solidify the solder; since rapid cooling can cause cracking due to thermal shock, a controlled cooling rate (typically 2–4°C / s) is maintained. If the cooling rate is too fast, residual stress occurs inside the solder, reducing bonding reliability, and if it is too slow, productivity decreases.
[0114] An important aspect of the present invention is that the SMT process is performed at a temperature of 185 degrees Celsius or higher, and the metal core substrate (100) dissipates heat generated during the SMT process and LED driving to prevent thermal deformation of the substrate, while ensuring a light transmittance of 60% or more through the transparent region (170). Since the melting point of aluminum is approximately 660 degrees Celsius, which is much higher than the reflow temperature, no substrate deformation occurs even in high-temperature processes. In addition, the metal core substrate (100) rapidly absorbs and disperses heat generated during the reflow process, thereby preventing localized overheating. This is particularly important for fine pixel pitches, as heat tends to concentrate during reflow due to the dense density of LEDs. The heat dissipation function of the metal core substrate (100) improves the uniformity of the reflow process and stabilizes the quality of the solder joint.
[0115] In step S30, the substrate is flipped over. The substrate is rotated 180 degrees so that the bottom surface is facing upward. This is a preparatory step for mounting an LED (160) on the bottom surface. When flipping the substrate, care must be taken to avoid damaging the LED (150) mounted on the top surface, and a dedicated flip jig or robot arm is generally used.
[0116] In step S40, a plurality of LEDs (160) are mounted in a second grid pattern on the copper pattern layer (140) of the lower surface using an SMT process so as to be positioned between the grid regions of the first grid pattern. This step basically uses the same SMT process as step S20, but is characterized by the fact that the arrangement pattern of the LEDs is different in that it is a second grid pattern, and the step of mounting the LEDs in the second grid pattern is characterized by precisely aligning the LEDs (150) on the upper surface and the LEDs (160) on the lower surface so that they do not overlap when projected vertically, and the overlap spacing distance between the upper surface LEDs (150) and the lower surface LEDs (160) is set so that the area ratio of the transparent region (170) is 60% or more of the total area, thereby maximizing the transparent region (170) while preventing mutual optical interference.
[0117] To achieve precise alignment, the coordinate systems of the upper and lower surfaces of the substrate must be accurately aligned. To this end, alignment marks (or fiducial marks) are formed on the substrate and are typically placed at diagonal positions on the substrate, such as in circular or cross-shaped copper patterns. The size of the alignment marks is generally 1-3 mm in diameter and must have high contrast with the surroundings so that the vision system can clearly recognize them. A pick-and-place machine uses a vision system to recognize the alignment marks and corrects the placement coordinates of the LEDs based on them. The vision system consists of a CCD or CMOS camera and an image processing algorithm, and uses pattern recognition technology to calculate the center coordinates of the alignment marks. When mounting the lower LED (160), the substrate is flipped over, so the coordinate system of the lower surface is established by referring to the alignment marks on the upper surface. Modern SMT equipment can simultaneously observe the upper and lower surfaces of the substrate using transmitted X-ray or infrared imaging, thereby achieving alignment precision of ±5 µm.
[0118] The placement coordinates of the second grid pattern are calculated based on the first grid pattern. For example, if the LEDs (150) of the first grid pattern are placed at positions (0, 0), (4mm, 0), (0, 4mm), and (4mm, 4mm), the LEDs (160) of the second grid pattern are placed at positions (2mm, 2mm), (6mm, 2mm), (2mm, 6mm), and (6mm, 6mm) so as to be positioned between the grid areas. Positional precision is very important because, in order to accurately implement this offset placement, they must be moved precisely by a distance corresponding to half the pixel pitch. The overlap spacing is optimized and set so that the area ratio of the transparent area (170) achieves 60% or more. For example, if the pixel pitch is 4mm and the LED package size is 2mm x 2mm, the area occupied by the LED is 4mm² and the pixel area is 16mm², so the LED area ratio is 25% and the transparent area (170) is 75%. The design is made so that the opaque area (LED mounting area + metal core substrate + insulating layer + copper pattern layer) is 40% or less by adjusting the overlap spacing.
[0119] After mounting the LED (160), a reflow process is performed again. At this time, it is important to note that the LED (150) already mounted on the upper surface of the substrate is exposed to high temperatures again. Generally, since LED packages are designed to withstand exposure to temperatures of 260 degrees Celsius or less for less than 10 seconds, this is not a problem if an appropriate reflow profile is used. However, since the upper surface LED (150) undergoes a second reflow thermal cycle, the thermal burden can be reduced by slightly lowering the peak temperature (230-240 degrees Celsius) or shortening the TAL time (30-60 seconds). Additionally, the heat dissipation function of the metal core substrate (100) helps to mitigate the temperature rise of the upper surface LED (150). In some embodiments, a thermal shield film may be attached to protect the upper surface, or a low-temperature solder paste (a Sn-Bi alloy with a melting point of about 138°C) may be used. By using low-temperature solder, the reflow temperature can be lowered to 160-180 degrees Celsius, which can significantly reduce the heat burden on the upper LED (150).
[0120] After all SMT processes are completed, an inspection process is performed. Inspection items include LED positioning accuracy, solder joint status, polarity errors, omissions, tilt, bridging (solder short circuits between adjacent pads), and balling (formation of unnecessary solder balls); 100% inspection is performed using Automated Optical Inspection (AOI) equipment. AOI equipment captures the substrate with a high-resolution camera and automatically detects defects using image processing algorithms. While AOI is generally based on 2D images, advanced systems can use 3D images to measure the height and volume of solder joints. 3D AOI utilizes structured light projection or laser triangulation methods. Detected defects are corrected during the rework process, which is performed manually using a soldering iron or a rework station. The rework station is a piece of equipment capable of localized heating, allowing for the selective heating and removal of defective LEDs, which can then be replaced with new ones.
[0121] Optionally, after mounting the LED, the method may further include the step of applying an optical adhesive layer (171) with a transmittance of 60% or more onto a transparent area (170), and the step of attaching a transparent glass (172) onto the optical adhesive layer (171). The application of the optical adhesive layer (171) can be performed by selecting from the various methods described above (OCA film lamination, OCR filling, sealant application, etc.). In an embodiment of the present invention, liquid OCR is applied to a transparent area (170) by a dispensing method, then bubbles are removed through a degassing process in a vacuum chamber, and then cured with UV. Dispensing is performed using a syringe or a jet dispenser, and the amount and location of application can be precisely controlled. Degassing is performed under conditions of a vacuum level of 1-10 torr and a time of 5-30 minutes, so that bubbles rise to the surface and are removed. UV curing is performed using a UV-LED with a wavelength of 365 nm or 395 nm under conditions of an illuminance of 10-50 mW / cm² and a time of 10-60 seconds.
[0122] The attachment of the transparent glass (172) can be performed before the optical adhesive layer (171) is cured (wet bonding) or after it is cured (dry bonding). Wet bonding is a method in which the transparent glass (172) is placed on the OCR while it is still in a liquid or semi-cured state, and then pressure is applied and the glass is cured, which minimizes the formation of bubbles. Dry bonding is a method in which the OCR is cured first, and then the transparent glass (172) is attached using an adhesive. When attaching the transparent glass (172), alignment precision and pressure uniformity are important, and dedicated lamination equipment is used. The lamination pressure is generally 0.5-5 bar, and the process is performed in a vacuum or inert gas (nitrogen) atmosphere to prevent the formation of bubbles. After attachment, final curing is performed, and the edges are sealed with a sealant to prevent moisture penetration.
[0123] The quality of the finally completed MCPCB board high-brightness double-sided transparent LED display is verified through electrical and optical tests. In electrical testing, the driving voltage, current, and resistance of each LED are measured to verify normal operation and detect short or open defects. Electrical testing is performed using a flying probe tester or a bed-of-nail tester. In optical testing, the brightness, color, and uniformity of each LED are measured using a colorimeter and a luminance meter. Color is expressed as x, y coordinates in the CIE 1931 color space, and the color deviation between LEDs is within the acceptable range (generally x, It checks whether it falls within y < 0.01. Luminance is measured for each pixel to evaluate uniformity, and generally, a uniformity of 95% or higher (ratio of minimum luminance to maximum luminance) is targeted. The measured data optimizes the brightness and color uniformity of the entire display by individually adjusting the driving current of each LED through a calibration process. This calibration data is stored in the display control system and applied during actual operation.
[0124] As a variation of the manufacturing method of the present invention, additional processes may be inserted between the steps described above. For example, a substrate inspection step may be added between step S20 and step S30. By inspecting the quality of the upper surface after the mounting of the upper surface LED (150) is completed and before mounting the lower surface LED (160), defects can be detected and corrected early. This is advantageous for improving process yield because it is difficult to rework the upper surface after mounting the lower surface. As another variation, a protective coating may be added after mounting the LED. The protective coating covers the LED and the copper pattern layer with a transparent epoxy resin, silicone resin, or parylene to protect them from moisture, dust, and chemicals. Parylene is an ultrathin polymer coating formed by the chemical vapor deposition (CVD) method, providing excellent moisture resistance, insulation, and uniformity. This is essential for displays used for long periods in outdoor environments, and the coating thickness is generally 10-50 µm. Spray coating, dipping, or curtain coating may be used as coating methods.
[0125] The MCPCB substrate high-brightness double-sided transparent LED display of the present invention can be manufactured in various sizes. Small displays are approximately 300mm x 300mm and are used for information boards or signage. Medium displays are approximately 1m x 1m to 2m x 2m and are used for store advertising or indoor exhibitions. Large displays are manufactured in sizes of several meters or more and are used for outdoor advertising or public information purposes. Large displays are generally manufactured in a modular manner, forming a large screen by connecting multiple MCPCB boards using a tiling method. Connections between modules utilize mechanical frames and electrical connectors, and they are precisely aligned to minimize seams at the module boundaries. The advantages of the modular design are that manufacturing, transportation, and installation are easy, parts can be replaced, and size expansion is freely possible.
[0126] The driving circuit is an electronic circuit designed to control an LED matrix and is generally composed of an LED driver IC, a microcontroller, and a power supply. The LED driver IC controls brightness by supplying a constant current to each LED and regulates grayscale using Pulse Width Modulation (PWM). PWM is a method that controls average brightness by turning LEDs on and off at a constant frequency (typically 1–10 kHz) and adjusting the duty ratio. For example, a duty ratio of 50% means the LED is on for half the time, so it is perceived as half brightness. Since a PWM frequency that is too low can cause flickering, a frequency of 1 kHz or higher is generally used. Representative LED driver ICs include TI's TLC59xx series, Maxim's MAX7219, and ICN's ICN2037. The microcontroller processes video data and transmits control signals to the LED driver IC; typically, ARM Cortex series or FPGAs are used. The ARM Cortex-M series is suitable for low-power and real-time processing, while the ARM Cortex-A series offers high performance and operating system support. Field-Programmable Gate Arrays (FPGAs) are semiconductors capable of programming hardware logic, making them advantageous for parallel processing and high-speed data transmission. Power supplies convert AC input to DC and provide a stable voltage; various capacities ranging from tens of watts to several kilowatts are used depending on the power consumption of the LEDs. Switching power supplies are generally employed, with an efficiency of 85–95%. The driving circuit can be installed on the back of the MCPCB board or in a separate control box, and is connected to the LED matrix via signal and power cables.
[0127] The display of the present invention can display various content. Static images include advertising posters, product photos, logos, etc., and dynamic images include video advertisements, animations, live broadcasts, etc.
[0128] Retry
[0129] Claude's response has been paused because the message length has reached the maximum limit. Please press Continue to resume Claude's response.
[0130] continue
[0131] Although the embodiments have been described above with reference to limited embodiments and drawings, those skilled in the art will understand that various modifications and variations are possible from the description above. Terms such as "include," "compose," or "have" as described above imply that components may be inherent unless specifically stated otherwise; therefore, they should be interpreted as allowing for the inclusion of additional components rather than excluding other components. Furthermore, the scope of protection of the present invention shall be interpreted by the claims below, and all technical concepts within an equivalent scope shall be interpreted as being included within the scope of rights of the present invention.
Claims
Claim 1 An MCPCB substrate high-brightness double-sided transparent LED display comprising: a metal core substrate made of aluminum material; an insulating layer formed on the upper and lower surfaces of the metal core substrate, respectively; a copper pattern layer formed on the insulating layer, respectively; and a plurality of LEDs mounted on the copper pattern layer, respectively; wherein the metal core substrate is selectively formed only in an opaque area where the LEDs are mounted, the LEDs on the upper surface are arranged in a first grid pattern, and the LEDs on the lower surface are arranged in a second grid pattern positioned between the grid areas of the first grid pattern, and the LEDs on the upper surface and the LEDs on the lower surface are arranged so as not to overlap upon vertical projection, so that the metal core substrate performs a heat dissipation function while providing electromagnetic shielding and optical blocking between the LEDs on the upper and lower surfaces, and a transparent area where the metal core substrate, insulating layer, and copper pattern layer are not formed is patterned and formed with an area ratio of 60% or more of the total area, thereby ensuring transparency while independently displaying images on the front and rear surfaces. Claim 2 An MCPCB substrate high-brightness double-sided transparent LED display, characterized in that, in claim 1, the transparent area is regularly arranged between the opaque area on which the LED is mounted, such that the opaque area occupies 40% or less of the total area and the transparent area occupies 60% or more of the total area. Claim 3 An MCPCB substrate high-brightness double-sided transparent LED display, characterized in that, in claim 1, the metal core substrate has a thermal conductivity of 200 W / mK or more. Claim 4 An MCPCB substrate high-brightness double-sided transparent LED display according to claim 1, wherein the insulating layer is formed of a composite material containing at least one of alumina, boron nitride, and aluminum nitride in an epoxy resin, has an insulating breakdown voltage of 2 kV or more, and the insulating layer is not formed in the transparent region to ensure light transmittance. Claim 5 An MCPCB substrate high-brightness double-sided transparent LED display, characterized in that, in claim 1, the light emission angle of the LED is limited to block optical interference between the light emission of one side LED and the light emission of the other side LED, and directional light emission control is performed such that the LED on the upper surface emits light only in the forward direction and the LED on the lower surface emits light only in the backward direction. Claim 6 An MCPCB substrate high-brightness double-sided transparent LED display characterized in that, in claim 1, the pixel pitch between the LEDs is 4 mm or less, and substrate deformation and pixel coordinate changes caused by heat generated during LED driving are suppressed by the heat dissipation characteristics of the metal core substrate, thereby stably realizing high brightness of 5000 nit or more while maintaining transparency through the transparent area. Claim 7 An MCPCB substrate high-brightness double-sided transparent LED display, characterized in that, in claim 1, an optical adhesive layer maintaining a transmittance of 60% or more is formed on the transparent region, and a transparent glass is attached on the optical adhesive layer to simultaneously secure mechanical strength and transparency. Claim 8 A step of preparing a metal core substrate made of aluminum material, wherein the LED mounting area is patterned and designed so that a transparent area occupies 60% or more of the total area; a step of patterning the metal core substrate so that the LED is selectively formed only in the opaque area where the LED is mounted, and forming an insulating layer on the upper and lower surfaces corresponding to the LED mounting area of the metal core substrate; a step of forming a copper pattern layer on the insulating layer; and a step of mounting a plurality of LEDs in a first grid pattern on the copper pattern layer on the upper surface using an SMT process. A method for manufacturing a high-brightness double-sided transparent LED display on an MCPCB substrate, comprising the step of mounting a plurality of LEDs in a second grid pattern on a copper pattern layer on the lower surface using an SMT process so as to be positioned between the grid regions of the first grid pattern, wherein the LEDs on the upper surface and the LEDs on the lower surface are arranged so as not to overlap when projected vertically, the SMT process is performed at a temperature of 185 degrees Celsius or higher, and the metal core substrate dissipates heat generated during the SMT process and LED driving to prevent thermal deformation of the substrate, while securing a light transmittance of 60% or more through the transparent region. Claim 9 A method for manufacturing a high-brightness double-sided transparent LED display on an MCPCB substrate, wherein, in claim 8, the step of mounting LEDs in the second grid pattern is characterized by mounting them in a position where the LED on the upper surface and the LED on the lower surface are precisely aligned so as not to overlap when projected vertically, and the overlapping spacing between the LED on the upper surface and the LED on the lower surface is set so that the area ratio of the transparent area achieves 60% or more of the total area, thereby maximizing the transparent area while preventing mutual optical interference. Claim 10 A method for manufacturing a high-brightness double-sided transparent LED display on an MCPCB substrate, characterized in that, in claim 8, after mounting LEDs on the upper and lower surfaces, it further comprises the steps of: applying an optical adhesive layer with a transmittance of 60% or more on a transparent area; and attaching a transparent glass on the optical adhesive layer.
Citation Information
Patent Citations
Wide-angle LED illuminating device
JP2011124207A
LED package and surface mounting technology
KR100826414B1
Method for manufacturing bilateral symmetry based-on transparent LED display divice
KR102025408B1
LED Heat-Radiating Substarte with Contains an Area with Filled by Underfill Material
KR102662113B1
